2021
DOI: 10.1002/adfm.202106715
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Sites Electrocatalysis in High‐Entropy Alloys

Abstract: High‐entropy alloys (HEAs) have attracted widespread attention in electrocatalysis due to their unique advantages (adjustable composition, complex surface, high tolerance, etc.). They allow for the formation of new and tailorable active sites in multiple elements adjacent to each other, and the interaction can be tailored by rational selection of element configuration and composition. However, it needs to be further explored in catalyst design, the interaction of elements, and the determination of active sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
135
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(160 citation statements)
references
References 215 publications
(357 reference statements)
0
135
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19] These active HEA interfaces consist of numerous atomic combinatorial arrangements, providing a rich local electronic structure potentially superior to the conventional catalysts. [20][21][22][23][24] It is known that noble metals play key roles in many catalytic reactions. [25] For example, Pt is super active for the hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR), and the RuO 2 and IrO 2 are considered as the best catalysts for the electrochemical oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] These active HEA interfaces consist of numerous atomic combinatorial arrangements, providing a rich local electronic structure potentially superior to the conventional catalysts. [20][21][22][23][24] It is known that noble metals play key roles in many catalytic reactions. [25] For example, Pt is super active for the hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR), and the RuO 2 and IrO 2 are considered as the best catalysts for the electrochemical oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%
“…14 The inherent synergistic effect among the various element components of HEAs can tune their electronic states, endowing HEAs with possible upgraded catalytic activity. [15][16][17][18] Meanwhile, their high entropy and sluggish diffusion effects greatly enhance their thermal and chemical stability and corrosion resistance, ensuring that HEAs can operate stably under harsh conditions. 19,20 For instance, Huang et al reported that PtRuNiCoFeMo HEA sub-nanometer nanowires (SNWs) with strong interactions between different metal sites exhibited good activity for the alkaline hydrogen oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…High-entropy alloy has been considered as the remarkable nonprecious metal-based OER electrocatalysts due to their adjustable composition, complex surface, enhanced wear resistance, etc. ( Li et al, 2021 ; Park et al, 2022 ; Han et al, 2022 ). More importantly, OER is a four-electron/four-proton reaction process and involves the adsorption/desorption of several intermediates (HO*, O*, and HOO*) on the catalyst surface.…”
Section: Regulation Of Active Site For Promoting Oermentioning
confidence: 99%